Musical Accompaniment in Dolalak Dance: The Perspective of Beauty Philosophy - Cita Hapsari, Maria Magdalena; Naam, Muh Fakhrihun (Universitas Negeri Semarang, 2023)
Dolalak is an art form that encompasses the integration of dance and music components. Dolalak, a widely known folk art form, continues to thrive in the local community of Purworejo Regency, located in the province of Central Java. This form of Dolalak art is classified within the collective folk art genre, serving as a distinctive representation of the artistic tradition found in Purworejo Regency. This research is of the qualitative descriptive type. The data collection technique employed in this research is document study. The data analysis technique in this research involves data collection, data reduction, data presentation, and drawing conclusions. The authenticity of the data is ensured through the technique of theoretical triangulation. The aesthetics of the music in Tari Dolalak reflect deep-seated cultural, religious, and creative values. Through harmony, rhythm, and emotional expression, the music in Tari Dolalak offers a captivating and profound artistic experience for its enthusiasts, solidifying this dance as an inseparable part of Indonesia's rich and valuable cultural heritage.